The role of bacterial symbionts in the biodegradation of chlorpyrifos in the digestive tract of Plutella xylostella larvae - Mochammad Syamsul Hadi; ABDUL LATIEF ABADI; TOTO HIMAWAN; MASRURI MASRURI; SAFIRA RIZKA LESTARI; BAMBANG TRI RAHARDJO; LUQMAN QURATA AINI; YOGO SETIAWAN; HAGUS TARNO (Society for Indonesian Biodiversity, 2021)
Abstract. Hadi MS, Abadi AL, Himawan T, MAsruri, Lestari SR, Rahardjo BT, Aini LQ, Setiawan Y, Tarno H. 2021. The role of bacterial symbionts in the biodegradation of chlorpyrifos in the digestive tract of Plutella xylostella larvae. Biodiversitas 22: 702-712. Several species in the order Lepidoptera act as plant pests, one of which is Plutella xylostella. Plutella xylostella is one of the most destructive pests of cabbage and other horticultural crops. The use of chemical insecticides as pest control for P. xylostella causes many problems, such as the increased pest resistance to pesticides. The objectives of this study are:  (i) to obtain and characterize symbiont bacteria in the digestive tract of P. xylostella collected from organic and conventional agriculture soils; (ii) to evaluate the potential of bacterial symbionts in the digestive tract of P. xylostella from organic and conventional soils in degrading the active ingredient of chlorpyrifos insecticide; (iii) To determine the biodegradation process of chlorpyrifos insecticide by symbiont bacteria in the digestive tract of P. xylostella; and (iv) to identify the derivative compounds from the biodegradation of chlorpyrifos insecticide. The results showed 30 symbiont bacteria isolated from the digestive tract of P. xylostella collected from organic soil and 36 symbiont bacteria isolated from the digestive tract of P. xylostella from conventional farming soil. There are 15 species of symbiont bacteria in 5 genera from the digestive tract of P. xylostella from organic and conventional farming capable of degrading the chlorpyrifos insecticide. They are identified as Providencia sp., Pseudomonas sp., Serratia sp., Proteus sp., and Aeromonas sp. Chlorpyrifos-derived compounds from the biodegradation of symbiont bacteria are less toxic than chlorpyrifos compounds.